Epigenetics of melanoma - Kwinta, Łukasz (Contemporary Oncology/Współczesna Onkologia, 2008)
Epigenetics describes the mechanisms that lead to changes in expression of genetic material not related to alterations in DNA sequences. Two processes with this association are DNA methylation and post-translational modifications of histones. DNA methylation concerns cytosines localized in CpG islands. This process changes interactions with DNA-binding factors. Histones can undergo post-translational modifications such as acetylation, methylation, phosphorylation, ubiquitination and sumoylation. The main effects of these modifications are alterations in chromatin structure and conformation. Many findings indicate that epigenetic events are crucial for carcinogenesis of various neoplasms, including melanoma. The genetic background of melanoma is still full of unanswered questions, with classical genetics able to explain only some melanoma cases. Novel advances concerning epigenetics give us new insight into melanoma carcinogenesis. This review focuses on recent reports and results in this field.